2003
DOI: 10.1002/bjs.4051
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Van Nuys Prognostic Index in prediction of recurrence of ductal carcinoma in situ after breast-conserving surgery

Abstract: Excision margin width is the most important predictor of local recurrence after breast-conserving surgery for DCIS. The VNPI lacked discriminatory power for guiding further patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…However, this result should be weighed up against the 12% rate observed at 5 years in a series of low-risk patients (Wong et al, 2006). On the other hand, the Van Nuys Prognostic Index (VNPI), combining tumour size, grade and margin width, was used to select 'low-risk' patients not requiring RT (Silverstein et al, 1996), but was widely criticised in two large American and English studies including 222 and 237 patients, respectively (Boland et al, 2003;MacAusland et al, 2007). A recent Italian study (Di Saverio et al, 2008) including 259 patients also used VNPI and concluded in the absence of statistically significant advantage in the CS þ RT vs the CS group.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result should be weighed up against the 12% rate observed at 5 years in a series of low-risk patients (Wong et al, 2006). On the other hand, the Van Nuys Prognostic Index (VNPI), combining tumour size, grade and margin width, was used to select 'low-risk' patients not requiring RT (Silverstein et al, 1996), but was widely criticised in two large American and English studies including 222 and 237 patients, respectively (Boland et al, 2003;MacAusland et al, 2007). A recent Italian study (Di Saverio et al, 2008) including 259 patients also used VNPI and concluded in the absence of statistically significant advantage in the CS þ RT vs the CS group.…”
Section: Discussionmentioning
confidence: 99%
“…The association of COX-2 expression with nuclear grade in DCIS confirms the findings of Shim et al (2003). Since nuclear grade is an independent marker of DCIS local recurrence (Silverstein et al, 1996;Boland et al, 2003a), further study is warranted to determine whether COX-2 is independent of grade with regard to the risk local DCIS recurrence following breast conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Classification systems based on various differentiation aspects of DCIS seem to be clinically relevant, as the nuclear grade is strongly associated with disease recurrence (Ringberg et al, 2000;Boland et al, 2003). Unfortunately, the interobserver reproducibility of the analyses is low (Douglas-Jones et al, 2000;Wells et al, 2000) and there is still a need for a more objective basis for the classification of DCIS.…”
mentioning
confidence: 99%